Pemikiran Teologi Pembebasan Islam H.O.S Cokrominoto - Ferdhiyadi N; Abd. Rahim Yunus; Syamzan Syukur (Universitas Negeri Makassar, 2023)
H.O.S Cokroaminoto was one of the pioneers of the national movement and was dubbed The Guru of the nation because he was a teacher for national figures, such as Sukarno, Muso, and Kartosuwiryo. Under the leadership of H.O.S Cokroaminoto, Sarekat Islam (SI) which used to focus only on economic movements then transformed into a political movement. Through the thought of Islamic Socialism, H.O.S Cokroaminoto made Sarekat Islam a political organization that fought against Dutch colonialism in order to achieve the path to the ideals of the independent state of Indonesia. This paper seeks to reveal the relationship of Islamic Liberation Theology thought popularized by Asghar Ali Engineer with Islamic Socialism thought H.O.S Cokroaminoto. The thought of Islamic Liberation Theology was born from theological reflection on social realities such as oppression, poverty, and injustice. The same is true of the Islamic Socialism thought formulated by H.O.S Cokroaminoto, can not be separated from the reality of Dutch colonialism against the people of Indonesia. Islamic Socialism and Islamic Liberation Theology attempt a critical look at the function of religion that does not focus solely on the formalities of ritual worship. Religion should be on the side of the weak and be a liberating solution to oppressive socio-economic structures.